The effects of emotional eating and negative framing on healthy food choices: a quasi-experimental study on college student participants using virtual reality - Sembiring, Mesy Safira Br; Undarwati, Anna (Jurnal Konseling dan Pendidikan, 2024)
Cases of obesity have increased significantly in recent years, triggering the risk of chronic diseases such as cardiovascular disease, diabetes, depression and cancer. One of the main factors is unhealthy food choices, so further research is needed to understand the factors that influence food preferences. This study aimed to evaluate the influence of emotional eating and negatively framed messages on healthy food choices, using a quasi-experiment method involving 135 participants. Data were analyzed using general linear models to identify significant patterns of relationships. The results showed that negatively framed messages had a significant influence on healthy food choices, although the effect was not very strong. In contrast, emotional eating showed no significant influence on healthy food choices. However, there was an interaction between negative framing and emotional eating that influenced healthy food choices, suggesting that individuals with emotional eating tendencies may respond differently to negatively framed messages compared to other individuals. This study highlights the importance of message-based approaches to promote healthier eating habits. The practical implications of the findings may provide guidance for designers of public health interventions to consider aspects of message framing as one of the strategies in health campaigns. Further research is recommended to explore additional factors, such as mood, body mass index, gender, emotion regulation, and individual food preferences during emotional eating. These results may contribute to the design of more effective health policies in reducing the prevalence of obesity and motivating people to make healthier food choices.